Ageing population has changed the nature of major thoracic injury. Issue 6 (2nd April 2019) - Ferrah, Noha; Cameron, Peter; Gabbe, Belinda; Fitzgerald, Mark; Judson, Rodney; Marasco, Silvana; Kowalski, Tanya; Beck, Ben
Abstract : Introduction: An increasing proportion of the major trauma population are older persons. The pattern of injury is different in this age group and serious chest injuries represent a significant subgroup, with implications for trauma system design. The aim of this study was to examine trends in thoracic injuries among major trauma patients in an inclusive trauma system. Methods: This was a retrospective review of all adult cases of major trauma with thoracic injuries of Abbreviated Injury Scale score of 3 or more, using data from the Victorian State Trauma Registry from 2007 to 2016. Prevalence and pattern of thoracic injury was compared between patients with multitrauma and patients with isolated thoracic injury. Poisson regression was used to determine whether population-based incidence had changed over the study period. Results: There were 8805 cases of hospitalised major trauma with serious thoracic injuries. Over a 10-year period, the population-adjusted incidence of thoracic injury increased by 8% per year (incidence rate ratio [IRR] 1.08, 95% CI 1.07 to 1.09). This trend was observed across all age groups and mechanisms of injury. The greatest increase in incidence of thoracic injuries, 14% per year, was observed in people aged 85 years and older (IRR 1.14, 95% CI 1.09 to 1.18). Conclusions: Admissions for thoracic injuries in the major trauma population are increasing. Older patients are contributing to an increase in major thoracic trauma. This is likely to have important implications for trauma system design, as well as morbidity, mortality and use of healthcare resources.